Ultrathin ceramic membrane capable of avoiding internal infiltration and preparation method thereof

By using agar hydrogel packaging technology on the ceramic support, the problem of infiltration of particles in the ceramic membrane layer is solved, and the preparation of ultra-thin ceramic membrane without infiltration is achieved, which improves the membrane flux and filtration accuracy, and reduces the preparation cost.

CN119684022APending Publication Date: 2025-03-25JIANGSU OPEN UNIVERSITY (THE CITY VOCATIONAL COLLEGE OF JIANGSU) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411860245.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

When building a traditional ceramic membrane, due to the large difference between the particle size of the membrane layer and the particle size of the support body, the particles of the membrane layer penetrate into the support body channel, affecting the integrity and filtration performance of the membrane. Moreover, the preparation of ultra-thin membrane layer ceramic materials is difficult.

Method used

By pretreating the ceramic support with ice and encapsulating the pores of the support with agar hydrogel, the membrane layer particles are prevented from infiltration, and then calcined after drying, an ultra-thin ceramic film can be prepared that can avoid infiltration.

Benefits of technology

The preparation of ultra-thin ceramic membranes without infiltration is achieved, which improves the flux and filtration accuracy of the membrane layer, reduces the preparation cost, and provides technical support for the development of high-performance ceramic membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684022A_ABST
    Figure CN119684022A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin ceramic membrane capable of avoiding internal infiltration and a preparation method thereof. The preparation method comprises the following steps: step S1, pretreating a ceramic support body with ice; s2, for the pretreated ceramic supporting body, supporting body pore channels of the ceramic supporting body are packaged with agar hydrogel; s3, coating the surface of the pore channel of the support body packaged by the agar hydrogel with a film coating liquid; and S4, calcining the ceramic support body coated with the film coating liquid to prepare the ultrathin ceramic film capable of avoiding internal infiltration. According to the invention, the pore channels of the support body are packaged by agar hydrogel, so that the ultrathin ceramic membrane capable of preventing membrane layer particles from infiltrating is prepared, and the membrane layer structure, binding force and the like are not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic membrane preparation, and in particular to an ultra-thin ceramic membrane capable of avoiding endosmosis and a preparation method thereof. Background Art

[0002] Ceramic membranes are widely used in oil-water separation, high-temperature dust removal and other fields due to their high mechanical strength, strong anti-pollution ability, high temperature resistance, and high pressure resistance. Traditional ceramic membranes include a membrane layer and a support body. The support body ensures the overall mechanical strength of the membrane, so the particle size is relatively large, while the membrane layer mainly plays a separation function and has a smaller particle size. Due to the significant difference between the particle size of the membrane layer and the particle size of the support body, when the membrane layer is constructed, the membrane layer particles will infiltrate into the pores of the support body, affecting the integrity of the membrane and even reducing the flux and filtration accuracy of the membrane. In addition, in order to achieve higher filtration flux and reduce operating energy consumption, there is a large demand for ultra-thin film ceramic materials, which makes the size of the membrane layer particles smaller, further increasing the difficulty of preparing such ceramic membranes.

[0003] In order to solve the problem of membrane particle infiltration, many scholars have conducted research. For example, Wei et al. [Journal of Membrane, 2017, 54: 381-390] sprayed a silicon carbide whisker layer on a silicon carbide support as a transition layer, which solved the problem of membrane infiltration. However, the thickness of the prepared ceramic membrane was 125 μm, and the silicon carbide whiskers still existed after high-temperature treatment, affecting the flux of the membrane. Later, Qiao et al. [Journal of Membrane Science, 2020, 594: 117464] used Al-DTPA (aluminum-diethylenetriamine pentaacetic acid) as a transition layer, which solved the problem of membrane infiltration and decomposed at high temperatures without affecting the membrane flux. However, the thickness of the prepared membrane was -100 μm; however, the materials used in these transition layers are relatively expensive and the membrane layer is relatively thick. Later, Ni et al. [Journal of Membrane Science, 2024, 695: 122496] prepared ceramic membranes by prefilling the pores of ceramic supports with PVB (polyvinyl butyral), which effectively achieved relatively low-cost and non-obvious infiltration membrane preparation, but the membrane thickness was still relatively thick, about 50 μm. In summary, there are still certain challenges in achieving the preparation of ultra-thin ceramic membranes without infiltration. Summary of the invention

[0004] The object of the present invention is to provide an ultra-thin ceramic membrane capable of avoiding internal seepage and a preparation method thereof.

[0005] To achieve the above purpose, the technical solution provided by the present invention is:

[0006] A method for preparing an ultra-thin ceramic membrane capable of avoiding infiltration comprises the following steps:

[0007] Step S1: pretreating the ceramic support with ice;

[0008] Step S2: encapsulating the support channels of the pretreated ceramic support with agar hydrogel;

[0009] Step S3: coating the coating liquid on the surface of the pores of the support body encapsulated by the agar hydrogel;

[0010] Step S4: drying the ceramic support coated with the coating liquid and then calcining it to obtain an ultra-thin ceramic membrane that can avoid internal infiltration.

[0011] The ceramic support is pretreated with ice, specifically: the ceramic support is horizontally placed on the substrate, flat ice cubes or flat ice bags are placed on the bottom of the substrate, so that the contact surface between the ceramic support and the substrate is kept at a low temperature and uniform; the low temperature is 0-2°C.

[0012] The substrate is a stainless steel plate, a quartz glass plate or a silicon carbide ceramic plate with a pore size of less than 5 μm with no obvious defects on the surface.

[0013] The agar solution is a 0.5-1.5wt% high-temperature agar aqueous solution at a temperature of 95-100 DEG C. The preparation method is: adding agar powder into water, sealing, heating and stirring at 95-100 DEG C for 25-35 minutes to completely dissolve the agar powder, and stopping stirring after the agar powder is completely dissolved but keeping heating for 5-10 minutes.

[0014] The method of encapsulating the support channels of the ceramic support with agar hydrogel is specifically as follows: dripping agar hydrogel solution drop by drop on the ceramic support so that the agar hydrogel solution penetrates into the pores of the ceramic support.

[0015] The method for judging whether encapsulation is complete is as follows: when the rate at which the agar hydrogel solution penetrates into the pores of the ceramic support is significantly reduced and obvious agar hydrogel is formed on the surface of the ceramic support, the pores of the support have been completely encapsulated by the agar hydrogel solution.

[0016] The coating liquid coated on the surface of the support channel encapsulated by the agar hydrogel solution is specifically a coating liquid containing solid particles such as silicon carbide with a particle size of 100-1000nm and a solid content of 25-40%.

[0017] The ceramic support coated with the coating liquid is dried and then calcined. The drying conditions are: drying at 30-50°C for 20-30h; the calcination conditions are: calcination temperature of 750-900°C, heating rate of 0.1-0.5°C / min, and insulation time of 1-2h.

[0018] The present invention also protects the ultra-thin ceramic membrane prepared by the method and capable of avoiding internal seepage.

[0019] The average pore size of the ultra-thin ceramic membrane is 50-800nm, and the membrane thickness of the ultra-thin ceramic membrane is 2-20μm.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention uses agar hydrogel to encapsulate the pores of the support body to avoid the infiltration of membrane layer particles. Due to the characteristics of the agar hydrogel, the membrane layer particles are piled up to form a stable structure during the drying process. When calcined at high temperature, 99% of the water in the agar hydrogel volatilizes at 100°C, and the remaining part decomposes at high temperature, which will not affect the membrane layer structure and bonding force, etc., and can achieve non-infiltration preparation of ultra-thin membrane layers.

[0022] The process of the invention is simple and pollution-free, and the agar raw material used is low-cost, which has great economic advantages in industrial production. The technology of the invention can realize the preparation of ultra-thin silicon carbide ceramic membranes with a particle size difference of a thousand times between the membrane layer particles and the support body particles, providing a technical reference for the development of high-performance ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The electron microscope images of the agar-encapsulated silicon carbide channels in Example 1 are: (a) an electron microscope image of the channels at the center position on the upper surface of the silicon carbide support, and (b) an electron microscope image of the channels at the edge position on the upper surface of the silicon carbide support.

[0024] Figure 2 These are cross-sectional electron micrographs of the ultrathin silicon carbide film layer prepared in Example 1: (a) a local cross-sectional electron micrograph of the ultrathin silicon carbide film at a magnification of 1000 times, and (b) a local cross-sectional electron micrograph of the ultrathin silicon carbide film at a magnification of 200 times.

[0025] Figure 3 This is the pore size distribution diagram of the ultra-thin silicon carbide membrane prepared in Example 1.

[0026] Figure 4 This is the flux change of the ultra-thin silicon carbide membrane prepared in Example 1 during oil-water separation.

[0027] Figure 5 These are the product pictures of comparative example 1: (a) an electron micrograph of the surface of the "silicon carbide membrane" after direct coating and calcination without agar encapsulation, and (b) an electron micrograph (cross-section) of the pores of the "silicon carbide membrane" after direct coating and calcination without agar encapsulation.

[0028] Figure 6 This is the product diagram of Comparative Example 2.

[0029] Figure 7These are the product pictures of comparative example 3: (a) a real picture of the "silicon carbide film" prepared using diethylenetriaminepentaacetic acid aluminum fiber as the transition layer, and (b) an electron microscope picture of the surface of the "silicon carbide film" prepared using diethylenetriaminepentaacetic acid aluminum fiber as the transition layer. DETAILED DESCRIPTION

[0030] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0031] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.

[0032] For the sake of simplicity, this document only specifically discloses some numerical values ​​and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.

[0033] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.

[0034] Some of the terms in the present invention are explained as follows:

[0035] The ultra-thin ceramic membrane layer in the present application refers to a ceramic membrane layer with a membrane thickness of less than 50 microns.

[0036] The present invention provides a method for preparing an ultra-thin ceramic membrane capable of avoiding internal seepage, comprising the following steps:

[0037] Step S1: pretreating the ceramic support with ice;

[0038] Step S2: encapsulating the support channels of the pretreated ceramic support with agar hydrogel;

[0039] Step S3: coating the coating liquid on the surface of the pores of the support body encapsulated by the agar hydrogel;

[0040] Step S4: drying the ceramic support coated with the coating liquid and then calcining it to obtain an ultra-thin ceramic membrane that can avoid internal infiltration.

[0041] In some embodiments, the ceramic support is pretreated with ice, specifically: the ceramic support is horizontally placed on the substrate, and flat ice cubes or flat ice bags are placed on the bottom of the substrate to keep the contact surface between the ceramic support and the substrate at a low temperature and uniform; the low temperature is 0-2°C.

[0042] In some embodiments, the substrate is a stainless steel plate, a quartz glass plate or a silicon carbide ceramic plate with a pore size of less than 5 μm having no obvious defects on the surface.

[0043] In some embodiments, the agar solution is a 0.5-1.5wt% high-temperature agar aqueous solution at a temperature of 95-100°C, and the preparation method is: adding agar powder to water, sealing, heating and stirring at 95-100°C for 25-35 minutes to completely dissolve the agar powder, and stopping stirring after the agar powder is completely dissolved but keeping heating for 5-10 minutes.

[0044] In some embodiments, the support pores of the ceramic support are encapsulated with agar hydrogel, specifically by dripping an agar hydrogel solution drop by drop on the ceramic support, so that the agar hydrogel solution penetrates into the pores of the ceramic support.

[0045] In some embodiments, the method for judging whether encapsulation is complete is: when the rate at which the agar hydrogel solution penetrates into the pores of the ceramic support is significantly reduced, and obvious agar hydrogel is formed on the surface of the ceramic support, the pores of the support have been completely encapsulated by the agar hydrogel solution.

[0046] In some embodiments, a coating liquid is coated on the surface of the support pores encapsulated by the agar hydrogel solution, specifically a coating liquid containing solid particles of silicon carbide with a particle size of 100-1000 nm and a solid content of 25-40%.

[0047] The coating liquid contains 50-70% water, 5-10% dispersant and surfactant, and the rest is silicon carbide.

[0048] In some embodiments, the ceramic support coated with the coating liquid is dried and then calcined. The drying conditions are: drying at 30-50°C for 20-30h; the calcination conditions are: calcination temperature of 750-900°C, heating rate of 0.1-0.5°C / min, and holding time of 1-2h.

[0049] The present invention also protects the ultra-thin ceramic membrane prepared by the method and capable of avoiding infiltration. The average pore size of the ultra-thin ceramic membrane is 50

[0050] -800nm, the film thickness of the ultra-thin ceramic film is 2-20μm.

[0051] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. This application takes a silicon carbide support with a ceramic support porosity of 30-50% and a pore size of 10-40 μm as an example:

[0052] Example 1

[0053] Weigh 0.8g agar and pour it into a beaker filled with 100ml deionized water. After placing the magnetic rotor, seal the top of the beaker with a silicone lid, then heat and stir at 100℃ for 30min until the agar is completely dissolved, turn off the stirring but keep heating. Then place a silicon carbide ceramic support (3cm in diameter, 4mm in height) with a porosity of 35% and a pore size of 20μm horizontally on a silicon carbide plate with a pore size of 3 microns and a flat ice cube on the bottom. Take 1ml of high-temperature agar solution with a rubber-tipped dropper and drop it drop by drop on the ceramic support (about 10 drops). Then apply a coating liquid with a solid content of 35% and a silicon carbide particle size of 500nm on the surface of the support, bake at 40℃ for 24h, and then send it into a muffle furnace and keep it at 900℃ for 1.5h, with a heating rate of 0.5℃ / min. The average pore size of the obtained ultra-thin silicon carbide membrane is 0.3 μm, the membrane thickness is 7 μm, and the pure water flux is 893 L·m -2 ·h -1 , the oil-water separation efficiency is 96%.

[0054] Example 2

[0055] Weigh 1.5g of agar and pour it into a beaker filled with 100ml of deionized water. After placing the magnetic rotor, seal the top of the beaker with a silicone lid, then heat and stir at 100℃ for 30min until the agar is completely dissolved, turn off the stirring but keep heating. Then place a silicon carbide ceramic support (3cm in diameter, 4mm in height) with a porosity of 50% and a pore size of 40μm horizontally on a stainless steel plate with a flat ice cube on the bottom. Use a rubber-tipped dropper to take 1.7ml of high-temperature agar solution and drop it drop by drop on the ceramic support (about 15 drops). Subsequently, a coating liquid with a solid content of 40% and a silicon carbide particle size of 100nm is coated on the surface of the support, baked at 40℃ for 24h, and then sent to a muffle furnace for insulation at 750℃ for 1.5h, with a heating rate of 0.3℃ / min. The average pore size of the obtained ultra-thin silicon carbide membrane is 80nm, the membrane thickness is 4μm, and the pure water flux is 119L·m -2 ·h -1 , the oil-water separation efficiency is 98%.

[0056] Example 3

[0057] Weigh 0.5g agar and pour it into a beaker filled with 100ml deionized water. After placing the magnetic rotor, seal the top of the beaker with a silicone lid, then heat and stir at 100℃ for 30min until the agar is completely dissolved, turn off the stirring but keep heating. Then place a silicon carbide ceramic support (3cm in diameter, 4mm in height) with a porosity of 30% and a pore size of 10μm horizontally on a quartz glass with a flat ice cube on the bottom. Use a rubber-tipped dropper to take 0.8ml of high-temperature agar solution and drop it drop by drop on the ceramic support (about 8 drops). Subsequently, a coating liquid with a solid content of 25% and a silicon carbide particle size of 1000nm is coated on the surface of the support, baked at 40℃ for 24h, and then sent to a muffle furnace for insulation at 900℃ for 1.5h, with a heating rate of 0.1℃ / min. The average pore size of the obtained ultra-thin silicon carbide membrane is 0.5μm, the membrane thickness is 12μm, and the pure water flux is 1055L·m -2 ·h -1 , the oil-water separation efficiency is 95%.

[0058] It can be seen from the above embodiments that the smaller the silicon carbide particle size, the lower the porosity of the formed membrane. High-temperature sintering will lead to over-sintering, causing the original pores to become smaller due to over-sintering.

[0059] Comparative Example 1

[0060] This comparative example is basically the same as the scheme of Example 1, except that agar encapsulation is not used, and the coating liquid is directly applied and then calcined. Test results: No continuous and complete film layer is formed on the surface of the support, and there is obvious infiltration and deposition of film layer particles in the pores of the support. This is because the pore size of the support is micrometer-level, while the particle size of the film layer particles used is nanometer-level. The coating liquid will directly infiltrate into the pores of the support under the action of capillary action and gravity, such as Figure 5 shown.

[0061] Comparative Example 2

[0062] This comparative example is basically the same as the scheme of Example 1, except that the agar hydrogel is replaced with PVB (8wt%) solution, and then the coating is calcined; the test results show that although the film layer has no obvious defects and the minimum film thickness is 40.95μm, the uniformity of the film layer is too poor. This is because the PVB solution has strong fluidity at room temperature. After the coating liquid is applied, the capillary force and its own viscosity value will cause the film layer particles to disperse, resulting in uneven film thickness, such as Figure 6 shown.

[0063] Comparative Example 3

[0064] Test results: This comparative example is basically the same as the scheme of Example 1, except that agar was not used for pore encapsulation, and aluminum diethylenetriamine pentaacetate fiber was used as a transition layer to avoid infiltration. Test results: The membrane layer was significantly damaged and bulged. This is because the fiber transition layer will reduce the contact between the nanoparticles and the support. During the calcination process, the membrane particles shrink, resulting in a lack of bonding between the membrane and the support, resulting in bulges, such as Figure 7 shown.

[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing an ultra-thin ceramic membrane capable of avoiding intravasation, characterized in that: The following steps are involved: Step S1: pretreating the ceramic support with ice; Step S2: encapsulating the support channels of the pretreated ceramic support with agar hydrogel; Step S3: coating the coating liquid on the surface of the pores of the support body encapsulated by the agar hydrogel; Step S4: drying the ceramic support coated with the coating liquid and then calcining it to obtain an ultra-thin ceramic membrane that can avoid internal infiltration.

2. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal infiltration according to claim 1, characterized in that: The ceramic support is pretreated with ice, specifically, the ceramic support is horizontally placed on the substrate, flat ice cubes or flat ice bags are placed on the bottom of the substrate, so that the contact surface between the ceramic support and the substrate is kept at a low temperature and uniform; the low temperature is 0-2°C.

3. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal infiltration according to claim 2, characterized in that: The substrate is a stainless steel plate, a quartz glass plate or a silicon carbide ceramic plate with a pore size of less than 5 μm with no obvious defects on the surface.

4. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal infiltration according to claim 1, characterized in that: The agar solution is a 0.5-1.5wt% high-temperature agar aqueous solution at a temperature of 95-100 DEG C. The preparation method is: adding agar powder into water, sealing, heating and stirring at 95-100 DEG C for 25-35 minutes to completely dissolve the agar powder, and stopping stirring after the agar powder is completely dissolved but keeping heating for 5-10 minutes.

5. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal seepage according to claim 1, characterized in that: The method of encapsulating the support channels of the ceramic support with agar hydrogel is specifically as follows: dripping agar hydrogel solution drop by drop on the ceramic support so that the agar hydrogel solution penetrates into the pores of the ceramic support.

6. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal infiltration according to claim 5, characterized in that: The method for judging whether encapsulation is complete is as follows: when the rate at which the agar hydrogel solution penetrates into the pores of the ceramic support is significantly reduced and obvious agar hydrogel is formed on the surface of the ceramic support, the pores of the support have been completely encapsulated by the agar hydrogel solution.

7. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal infiltration according to claim 1, characterized in that: The coating liquid coated on the surface of the support channel encapsulated by the agar hydrogel solution is specifically a coating liquid containing solid particles such as silicon carbide with a particle size of 100-1000nm and a solid content of 25-40%.

8. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal seepage according to claim 1, characterized in that: The ceramic support coated with the coating liquid is dried and then calcined. The drying conditions are: drying at 30-50°C for 20-30h; the calcination conditions are: calcination temperature of 750-900°C, heating rate of 0.1-0.5°C / min, and insulation time of 1-2h.

9. An ultra-thin ceramic membrane capable of avoiding internal seepage prepared by the method according to any one of claims 1 to 8.

10. The method for preparing an ultra-thin ceramic membrane capable of avoiding internal seepage according to claim 9, characterized in that: The average pore size of the ultra-thin ceramic membrane is 50nm-800nm, and the membrane thickness of the ultra-thin ceramic membrane is 2-20μm.